The Effects of Silkworm Excrement Organic Fertilizer on the Hemp Yield - Małgorzata Łochyńska; Jakub Frankowski (Journal of Natural Fibers, 2022)
The ecological farming and organic fertilization are getting popular and required in time, when synthetic fertilizers and agrochemicals are used and easily overcome. In this article, organic farming of hemp (Cannabis sativa L.) is presented, and an innovative organic fertilizer the mulberry silkworm (Bombyx mori L.) breeding waste is examined. This insect breeding is a cheap source of waste, which gives very positive results on the plants yield. Such tests of hemp have not been carried out so far. In this research, three repetition pots were prepared: with silkworm fertilizer 15 Mg∙ha−1, 30 Mg∙ha−1, and pots without fertilization (control). The amounts of three yields – total, straw, and seed – were measured. Moreover, the chemical composition of silkworm waste, soil, and hemp material was tested. The best results of fertilization were obtained in silkworm manure fertilization in dose 30 Mg∙ha−1.